2012
DOI: 10.1074/jbc.m112.352245
|View full text |Cite
|
Sign up to set email alerts
|

β-Subunit of the Ostα-Ostβ Organic Solute Transporter Is Required Not Only for Heterodimerization and Trafficking but Also for Function

Abstract: Background: Deletion of Ost␣-Ost␤, an intestinal transporter that participates in the enterohepatic circulation of bile acids, lowers cholesterol and triglyceride levels. Results: Residues of Ost␤ required for interaction with Ost␣ and transport activity were identified. Conclusion: Distinct regions of Ost␤ are essential for Ost␣-Ost␤ trafficking and transport activity. Significance: Findings suggest strategies for inhibiting the holotransporter and reducing lipid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…. It has been shown that OSTβ is important for both the trafficking of OSTα to the plasma membrane as well as for its function . However, the lack of co‐immunoprecipitation of the mature, glycosylated form of OSTα upon immunoprecipitation of OSTβ suggests that the primary interaction may occur early in the biosynthetic pathway and may be transient .…”
Section: Discussionmentioning
confidence: 99%
“…. It has been shown that OSTβ is important for both the trafficking of OSTα to the plasma membrane as well as for its function . However, the lack of co‐immunoprecipitation of the mature, glycosylated form of OSTα upon immunoprecipitation of OSTβ suggests that the primary interaction may occur early in the biosynthetic pathway and may be transient .…”
Section: Discussionmentioning
confidence: 99%
“…After secretion into the intestinal lumen, bile acids are efficiently taken up into ileocytes via the ASBT; their subsequent efflux across the basolateral membrane, a requirement for return to the liver via the portal circulation, is mediated largely by OST␣-OST␤. OST consists of two subunits that heterodimerize for membrane delivery and generation of transport activity (2,4,15,31,33,37). OST␣-OST␤ was originally implicated in the basolateral efflux of bile acids in the ileum on the basis of its substrate specificity, tissue distribution, subcellular localization, and transcriptional regulation (2,5).…”
mentioning
confidence: 99%
“…The organic solute transporter α‐β (OSTα‐OSTβ) is responsible for secretion of bile salts and conjugated steroids across the basolateral membrane of hepatocytes into the portal circulation . OSTβ is critically required for transport activity of the OSTα‐OSTβ heterodimer . The nuclear receptor FXR is considered the main regulator of OSTα and OSTβ expression .…”
Section: Discussionmentioning
confidence: 99%